Examination of lead absorption ability on chernozem soil and the observation of the accumulation effect of Lactusa sativa L. in pot experimentation - Sárközi, Edit; Kardos, Levente; Sepsi, Panna; Varga, Zsolt; Bisztray, György; Kátai, János (Acta Agraria Debreceniensis, 2014)
In our research a chernozem soil sample formed on loess was collected from an area under cultivation. Our aim was to determine the lead adsorption capacity using a soil column experiment. The study showed saturation of lead content of the soil. The lead accumulation capacity of Lactuca sativa L. was measured in the sections of roots and leaves applying pot experiments. It could be observed that the lettuce accumulated lead easily from the chernozem soil. The lead content was increased in the analyzed sections of the plants against an increasing lead content.